Two new species of Chelifera Macquart from China (Diptera: Empididae) - Wang, Xiwei; Yan, Shanchun; Yang, Ding (Zootaxa, 2014)
Two new Chelifera species, C. liuae sp. nov. from Sichuan and C. tibetensis sp. nov. from Tibet, are described. The genus Chelifera is recorded from Tibet for the first time. Cheliefera tibetensis is assigned to the C. rhombicercus-group. An updated key to the species of Chelifera from China is provided.